Misinformation, Health Literacy, and Vaccine Hesitancy: Implications for Public Policies - Verônica Mascarenhas Oliveira; Cláudio Eduardo Sousa Lima; Márcia Aparecida Silva Araújo; Marluce Amâncio de Araújo Mamede; Lenita da Silva Ferreira; Suzana Santos da Costa; Thaita Thaisi Zago; Sérgio Raimundo Ernesto Machado (RSV, 2026)
Vaccination represents one of the most effective public health interventions for preventing infectious diseases and reducing morbidity and mortality worldwide. However, vaccine hesitancy has emerged as a major challenge for immunization programs, influenced by misinformation, distrust in institutions, communication failures, and unequal levels of health literacy. The rapid expansion of digital communication platforms has transformed the circulation of health information, creating new opportunities for education while also facilitating the dissemination of inaccurate or misleading content. This scenario has significant implications for public policies, particularly regarding the maintenance of vaccination coverage and the protection of population health. This academic essay analyzes the relationship between misinformation, health literacy, and vaccine hesitancy, emphasizing their implications for public health policies and immunization strategies. The discussion explores the social and informational factors associated with vaccine confidence, the role of health literacy in enabling informed decision-making, and the challenges faced by governments and healthcare systems in responding to misinformation. The manuscript highlights that addressing vaccine hesitancy requires integrated approaches combining evidence-based communication, community engagement, trust-building, and policies capable of strengthening health systems' ability to respond to contemporary information challenges.